Hubungan antara amalan operasi perkhidmatan dengan prestasi Tentera Darat Malaysia (TDM) : gaya kepimpinan sebagai moderasi - Mat, Azmi (2016)
A study on delivery of services in the public sector in general and army in particular is insufficient. This study focuses on the level of service operations practices adopted by Malaysian Army and its relationship with performance. It aims to determine the relationship between the practice of service operations with the performance of the Malaysian Army in Peninsular Malaysia. In addition, this study also aims to identify whether leadership style acts as a moderator in the relationship between the practice of service operations with the performance of the Malaysian Army. Research method carried out was in the form of field study in which questionnaires were used as instrument. Data were analyzed using Pearson correlation, multiple regression and hierarchical regression analysis. 800 sets of questionnaires were sent to a unit in the organization of the Army of Malaysia with a return rate of 244 sets (30.5%). Data collected through questionnaires were analyzed using Statistical Package for Social Science (SPSS).The findings show a significant relationship between the dimensions of the practice of some service operations such as leadership practice, relationship oriented, the process of delivering a uniform, customer participation with the performance of the Malaysian Army. In addition, variables moderation leadership style namely transformational leadership style and transactional leadership style also affect the relationship between the practice of service operations with the performance of the Malaysian Army. The results of this study may contribute to the development of theory and knowledge in influencing the performance of the Malaysian Army to the proliferation of knowledge related to the field of operations management, especially help the Malaysian Army in the implementation of the operational management more efficiently and effectively.